Effect of polymer viscosity on physicochemical properties and ocular tolerance of FB-loaded PLGA nanospheres - Araújo, J. (2020)
Poly(lactide-co-glycolide) acid (PLGA) nanospheres incorporating flurbiprofen (FB) were produced by the solvent displacement technique, for ocular applications aiming to avoid/minimize inflammation induced by surgical trauma. In this work, a PLGA of low viscosity has been tested and the results obtained were compared with those previously reported by Vega et al. The physicochemical properties of the developed formulations were evaluated by measuring particle size, zeta potential and FB entrapment efficiency, showing no significant differences. Release studies demonstrated that the formulation produced with PLGA of higher viscosity revealed a slower drug release rate. Stability analysis, for a period of 75 days, was performed using three complementary methods: (i) turbidity experiments using a Turbiscan optical analyzer, (ii) particle size measurements, and (iii) zeta potential analysis. The results revealed long-term physicochemical stability suitability for ophthalmic use, being independent from the polymer viscosity. The ocular tolerance was assessed by an alternative in vitro method to animal experimentation, the HETCAM. For all developed formulations no ocular irritancy has been detected.